Road trauma among young Australians: Implementing policy to reduce road deaths and serious injury. (19th May 2017) - Walker, Clara; Thompson, Jason; Stevenson, Mark
ABSTRACT: Objective : The objective of this study was to estimate the likely reduction in road trauma associated with the implementation of effective interventions to reduce road trauma among young Australians. Methods : A desktop evaluation was conducted to model the likely reduction in road trauma (deaths and serious injuries resulting in hospitalization) among young people aged 17–24 years residing in Queensland, New South Wales, and Victoria. Potential interventions were identified using a rapid literature review and assigned a score based on evidence of effectiveness and implementation feasibility with the 3 highest scoring interventions included in the modeling. Likely reduction in road trauma was estimated by applying the average risk reduction effect sizes for each intervention to baseline risk (passenger or driver death or serious injury per 100, 000 population) of road trauma for young Australians. Point estimates were calculated for the potential number of deaths and serious injuries averted in each state and per 100, 000 population, with a one-way sensitivity analysis conducted using uncertainty ranges identified. Results : Peer passenger and night driving restrictions as well as improved vehicle safety measures had the greatest potential to reduce road trauma. Peer passenger restrictions could avert 14 (range: 5–24) and 24 (range: 8–41) hospitalizations per year in Queensland and New South Wales, respectively, and night driving restrictions could avert 17 (range: 7–26), 28 (range: 12–45), and 13 (range: 6–21) hospitalizations annually in Queensland, New South Wales, and Victoria. These interventions reduced fatalities by less than 1 death annually in each state. Improved vehicle safety measures could avert 0–3, 0–4, and 0–3 deaths and 3–91, 4–156, and 2–75 hospitalizations in Queensland, New South Wales, and Victoria. Conclusions : Key elements of graduated licensing (peer passenger and night driving restrictions) along with vehicle safety interventions offer modest but practically significant reductions in road trauma for young Australians. State governments need to revise current legislation to ensure that these reductions in road trauma can be realized.